Manipulation of flowering time and branching by overexpression of the tomato transcription factor SlZFP2. Issue 12 (29th June 2016) - Weng, Lin; Bai, Xiaodong; Zhao, Fangfang; Li, Rong; Xiao, Han
Summary: Flowering of higher plants is orchestrated by complex regulatory networks through integration of various environmental signals such as photoperiod, temperature, light quality and developmental cues. In Arabidopsis, transcription of the flowering integrator gene FLOWERING LOCUS T ( FT ) that several flowering pathways converge to is directly regulated by more than ten transcription factors. However, very little is known about the transcriptional regulation of the FT homolog SINGLE FLOWER TRUESS ( SFT) in the day‐neutral plant tomato ( Solanum lycopersicum ). Previously, we showed that the zinc finger transcription factor SlZFP2 plays important roles in regulation of seed germination and fruit ripening in tomato and also found that overexpression of SlZFP2 impacted flowering and branching. Here, we characterized in detail the early flowering and high branching phenotypes by overexpression of this transcription factor. Our data showed that overexpression of SlZFP2 accelerated flowering in an SFT ‐dependent manner as demonstrated by elevated SFT expression in the leaves and the transcription factor's binding ability to SFT promoter in vitro and in vivo . Furthermore, overexpression of the SlZFP2 gene in the sft plants failed to rescue the mutant's late flowering. Through analysis of grafting phenotype, growth response of branches to auxin application and transcriptome profiling by RNA sequencing, we also showed that overexpression of SlZFP2 affected shoot apical dominance through multiple regulatory pathways. Our results suggest that the transcription factor SlZFP2 has potential applications in genetic modification of plant architecture and flowering time for tomato production and other crops as well.